Self-supporting highly lithiated porous flexible 3D bulk anode for lithium metal secondary batteries

By using a self-supported, porous, 3D, flexible main anode in the lithium metal anode, and forming a silver (Ag) dendrite layer through electrochemical lithiation and replacement reaction, the problems of dendrite growth and uneven lithium plating in the secondary battery are solved, and uniform density lithium plating and peeling under high current density and high area capacity are achieved, which improves safety and supports fast charging.

CN119812210APending Publication Date: 2025-04-11THEION GMBH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411414060.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-10-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium metal anodes have defects such as dendrite growth, uneven lithium plating and peeling, mossy lithium formation, infinite volume changes during charging, and dead lithium formation in secondary batteries, which limit their application, and the existing solutions cannot achieve long-term cycle stability or fast charging.

Method used

Using a self-supported, porous, 3D, flexible body anode, which has an open porosity of at least 70% and a thickness of 10 μm to 100 μm, contains fibers with a diameter of 200 nm to 40 μm and a major lithium-philic constituent material showing a dendrite morphology, a silver (Ag) dendrite layer is formed by electrochemical lithiation and replacement reactions, enhancing the surface area of ​​the porous body for nucleation and alloying reactions with lithium.

Benefits of technology

It realizes uniform dense lithium plating and peeling at high current density and high area capacity, alleviates dendrite problems, improves the safety of lithium metal anodes, and supports fast charging and discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812210A_ABST
    Figure CN119812210A_ABST
Patent Text Reader

Abstract

A self-supporting, porous, 3D, flexible bulk anode for a lithium metal secondary battery, the self-supporting, porous, 3D, flexible bulk anode having gt; 5 atomic percent by weight of a primary coating, plus lt; 5 atomic weight% of at least two additional lithium-philic elements, resulting in a synergistic electroplating and stripping effect of alkali metal ions, in which all coating elements have the ability to form an intermetallic alloy with lithium and / or between them within a potential window range of 1.5 V to-0.5 V (relative to Li / Li +); having a porosity of at least 70%, and a thickness of 10 [mu] m to 100 [mu] m; non-woven, woven or ordered arrangement comprising constituent fibers having a diameter in the range of 200 nm to 40 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a self-supporting, porous, 3D, flexible host anode of a lithiophilic component with a dendritic morphology for lithium metal secondary batteries, a method for its preparation, and a secondary battery comprising the same (according to the independent patent claims).

[0002] There is a global demand for high energy density energy storage devices not only for mobile storage applications, but also for stationary storage applications. In particular, the electric vehicle industry has seen a rise in demand for mobile high energy density storage devices that can provide a pure electric vehicle with a range of 1000km after a single charge. In addition, energy storage devices with fast charging capabilities are highly sought after, requiring a charging time of less than 30 minutes to reach a 10% to 100% state of charge.

[0003] For mobile energy storage, lithium-ion batteries are a favorable choice due to their high cycle life and high voltage (depending on the anode and cathode potentials). In the state of the art of lithium-ion technology, an intercalation-based graphite negative electrode (anode) is used, which not only provides a low theoretical specific capacity of 372 mAh / g, but also provides limited charging rate capabilities.

[0004] The low charging rate is due to the fact that lithium ions (Li + ) slowly diffuses (i.e., embeds) into the bulk anode graphite structure. In addition, the high polarization gradient formed within the electrolyte during charging not only limits the Li + The accessibility of Li+ and Li+ also induces dendrite formation in this graphite-based anode due to the anode potential being driven below 0 V (i.e., the lithium plating potential). This means that within this host anode graphite structure, lithium plating becomes more likely than Li+. + Embedding is more advantageous.

[0005] To achieve the goal of high energy density batteries, it is ideal to use lithium metal as the anode and couple it with a high voltage cathode (e.g., LiNiPO4). Li metal as the negative electrode not only provides an order of magnitude higher specific capacity than graphite (3860 mAh / g), but also provides the lowest redox potential of -3.04 V (relative to the standard hydrogen electrode (SHE)). In addition, among all alkali metals, lithium metal provides the lowest density, i.e., 0.534 g / cm 3 In comparison, the prior art graphite anode has an operating potential of 0.1 V (relative to metallic lithium anode) and a carbon content of 2.26 g / cm 3 density.

[0006] Therefore, as the negative electrode, the metallic lithium anode becomes the holy grail anode.

[0007] However, as anode, lithium metal also suffers from several defects such as dendrite growth, uneven lithium plating and stripping, mossy lithium formation, unlimited volume change during charging, and dead lithium formation, which limit its application in commercial batteries despite its obvious advantages.

[0008] However, lithium remains a favorable candidate as an anode due to its ability to achieve high energy density batteries. To date, different approaches have been attempted to address the aforementioned deficiencies of lithium metal anodes.

[0009] For example, patent EP 3 852 171 A1 discloses a protective coating on a lithium metal anode that allows current densities up to 1 mA / cm 2 , area capacity is 1 mAh / cm 2 However, the current density is significantly lower, allowing even the prior art cathode (where 3.5 mAh / cm 2 or higher area capacity) for 1C charging.

[0010] Similarly, patent number US-9722275-B2 discloses nanostructuring of lithium metal anode with oxide particles to form a protective layer (which means an additional layer of inactive material) on the lithium metal anode, thus resulting in a lower weight energy density of the resulting secondary battery. In addition, this oxide layer can also react with lithium during charging, resulting in the formation of an interfacial layer (solid electrolyte interface (SEI)) that can inherently resist lithium ion transport, thus increasing the overall battery resistance.

[0011] In addition, several research articles mentioned the possibility of using conductive hosts with lithiophilic coatings to realize lithium metal batteries, but failed to successfully achieve current densities comparable to 1C charging (corresponding to state-of-the-art transition metal-based cathodes with respectable cycle life) (Chen, X.-R., Li, B.-Q., Zhao, C.-X., Zhang, R., Zhang, Q., Synergetic Coupling of Lithiophilic Sites and Conductive Scaffolds for Dendrite-Free Lithium Metal Anodes. Small Methods 2019, 1900177, https: / / doi.org / 10.1073 / pnas.1518188113 ).

[0012] It is therefore evident that, despite significant progress, there is still no concrete solution for implementing lithium metal as an anode within a secondary energy storage device. For example, protective coatings implemented on lithium metal do not provide long-term cycling stability or the possibility of fast charging. Furthermore, although different host structures have been described (such as carbon fibers or carbon nanotubes), these do not allow for long-term stability or high charging rates. Furthermore, most of these solutions have a high charge / discharge rate of 1 mA / cm 2 In addition, this body still requires a current collector foil, which adds weight to the dead material within the battery.

[0013] The lithium metal anode has 2061 mAh / cm 3 Theoretical volumetric capacity of lithium is 2061 mAh / cm2, but this corresponds to the fully dense state of lithium metal foil. Upon cycling, the lithium starts to form a moss-like structure, in which it creates voids and defects in the lithium metal foil. Ultimately, this reduces the volumetric capacity. Furthermore, it is quite common to use at least 100% excess lithium in the battery. For prior art batteries, lithium can be considered a "consumable" just like the electrolyte due to its side reactions. The N / P ratio defines the energy density and cycle life until complete depletion of the lithium in the battery and / or drying up of the electrolyte occurs. The theoretical volumetric capacity of lithium is 2061 mAh / cm2. 3 , but only for the first discharge cycle. To extend the cycle life, an additional 100% excess Li is required to compensate for the side reactions. The achievable volume capacity is then about 1030 mAh / cm 3 But this volumetric capacity will be further reduced due to irreversible volume fluctuations / fragmentation of lithium (i.e., moss-like structure and dead lithium formation). Taking this into account, this reduces the volumetric capacity of lithium metal anodes to close to LiC6 graphite 747 mAh / cm 3 , which means that current lithium metal technology has no advantages over existing technology batteries.

[0014] Potential solutions to provide bulk lithium metal anodes for secondary batteries have been proposed to alleviate the deficiencies mentioned above.

[0015] Document US2020 / 274155 A1 discloses an anode comprising: a first layer comprising a porous 3D polymer structure exhibiting a porosity between 60 and 90%; and a second layer comprising lithium metal, wherein the first layer comprises a polymer and the particles comprise at least one of copper and nickel, and the surface is coated or doped with at least one of Sn, Zn, Bi, In, Ga, Al, Si, Ge.

[0016] Document WO 2021 / 189083 A1 discloses a battery in which the anode has a lithium-philic fiber skeleton with an open porosity of at least 70%, a polymer liner, the fibers having a diameter of less than 0.5um, and further comprising a lithium-philic surface coating composed of oxides, nitrides, polymers and ceramics deposited thereon, whereby the group of oxides consists of niobium oxide, AlzO+ZnO, indium oxide, zinc oxide, bismuth oxide, magnesium oxide, silicon oxide, gold oxide, iodine oxide and sulfur oxide.

[0017] Document US2017 / 352868 A1 discloses an anode for a lithium secondary battery, which comprises an integral 3D graphene-carbon-metal hybrid foam consisting of a plurality of pores, pore walls, and a lithium-attracting metal or a lithium-philic metal, wherein the lithium-attracting metal or the lithium-philic metal is selected from Au, Ag, Mg, Zn, Ti, Na, K, Al, Fe, Mn, Co, Ni, Sn, V, Cr, and Ni, and the amount is between 0.1 and 90%.

[0018] Document XP087396814 (Yue Chen et al., New Carbon Materials, 01-08-2023, 38(4), 698-724, doi:10.1016 / S1872-5805(23)60734-6) relates to different lithium metal anodes, in particular to silver used as a lithiophilic component, which is coated on different 3D porous supports such as CNF ni

[91] , porous carbon skeleton ni

[92] or graphene ni

[94] .

[0019] Document XP086242704 (Yu Ye et al., Journal of Power Sources 472, p 1-9, 16-07-2020, doi: 10.1016 / jpowsour.2020.228520) discloses a 3D substrate (3D Li-Zn@Cu foam) functionalized with a Li-Z lithiophilic alloy surface by electrochemically depositing Zn on Cu foam. This substrate can induce uniform Li deposition along the conductive skeleton, effectively reduce the Li nucleation overpotential, and inhibit Li dendrite formation.

[0020] However, there is still a lot of room for improvement and for solutions that are easy and economical to manufacture and implement.

[0021] This object is solved by a self-supporting, porous, 3D, flexible main body anode, a method for preparing a self-supporting, porous, 3D, flexible main body anode, and a secondary battery using a self-supporting, porous, 3D, flexible main body anode, wherein the elements are as contained in the independent claims and the preferred embodiments are described by the elements of the dependent claims.

[0022] Provided is a self-supporting, porous, 3D, flexible main body anode for a lithium metal secondary battery, the self-supporting, porous, 3D, flexible main body anode having an open and accessible porosity of at least 70% and a thickness in the range of 10 μm to 100 μm, comprising a non-woven, woven or ordered arrangement of fibers having a diameter in the range of 200 nm to 40 μm, and comprising a main lithium-philic constituent material exhibiting a dendritic morphology and a small amount of at least two additional lithium-philic materials, wherein the concentration of these additional lithium-philic materials is less than 5 atomic weight %, and wherein electrochemical lithiation results in the formation of one or more intermetallic alloys, thereby resulting in a high lithiated state, i.e., exceeding the theoretical lithiated capacity of the existing intermetallic phase, which results in the coexistence of two phases (i.e., the intermetallic alloy and lithium metal).

[0023] Preferably, the primary dendrite-forming material comprises a noble metal grown via a replacement or substitution reaction of an underlying less noble metal. More preferably, the noble metal is silver (Ag) and has a small amount of a second lithiophilic component comprising palladium (Pd), tin (Sn) and / or magnesium (Mg).

[0024] Even more preferably, silver (Ag) is provided as a constituent layer comprising dendrites, thereby increasing the redox active surface area of ​​the porous bulk anode for nucleation and alloying reactions with lithium.

[0025] The specific low concentration of secondary lithiophilic heteroatoms / species and the primary lithiophilic dendrite-like constituent layers on the surface of the porous 3D flexible host are capable of forming continuous intermetallic transition compounds with lithium and / or between them, i.e., secondary or tertiary alloys with high lithiation (i.e., exceeding the theoretical lithiation capacity of the existing intermetallic phase), which enables lithium to initially diffuse rapidly within the electrochemically formed alloy, followed by lithium plating on top of the formed intermetallic phase after reaching the solubility limit of the alloy formed at high areal capacity.

[0026] Initially, upon lithiation and subsequent hyperlithiation, the constituent heteroatoms react with lithium to form intermetallic phases with and / or between lithium, thereby forming suitable nucleation centers for subsequent lithium deposition during lithium electroplating. The synergistic porous 3D design of the host enables uniform and dense lithium plating and stripping at high current density and areal capacity.

[0027] The synergistic effect between the lithiophilic dendritic morphology of silver (Ag) on ​​the 3D host enables the high performance of the host described herein. The dendritic silver (Ag) layer enhances the interaction area between the plated lithium ions and the lithiophilic heteroatoms / species, thereby allowing for enhanced active alloying sites and low nucleation potential, while the 3D porous morphology of the host itself enables a uniform electric field across the host, thereby facilitating interaction with incoming or plated lithium ions, thereby helping to eliminate the so-called "lightning rod effect", and wherein the coating element has a high conductivity over a range of 1.5V to -0.5V (vs. Li / Li + ) within the potential window of 200 Å to 400 Å and / or to form intermetallic alloys between lithium / sodium and between them.

[0028] The present invention paves the way for lithium metal anode secondary batteries with high C-rate capability, balanced N / P capacity ratio (lithium excess less than 50%), and fast charge / discharge, which have enhanced safety due to the alleviation of the dendrite problem commonly observed in secondary lithium metal anode batteries.

[0029] The bottom fiber of the self-supporting, porous, 3D, flexible host anode can be composed of metallized polymer fibers such as polyacrylonitrile (PAN), polypropylene (PP), polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK) or polyethersulfone (PES), which are stable to organic liquid electrolytes, polymer electrolytes, gel polymer electrolytes or ceramic electrolytes and lithium salts commonly used in secondary lithium metal or lithium ion batteries.

[0030] Also provided is a method for preparing a self-supporting porous 3D main body anode for a lithium metal secondary battery, the method comprising the following steps: providing a polymer fiber, such as polyacrylonitrile (PAN), polypropylene (PP), polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK) or polyethersulfone (PES), the polymer fiber having a diameter of 200nm to 40μm and being stable to an organic liquid electrolyte, a polymer electrolyte, a gel polymer electrolyte or a ceramic electrolyte and a lithium salt commonly used in secondary lithium metal or lithium ion batteries, forming a nonwoven, woven or ordered fabric from the polymer fiber, the fabric having to The invention relates to a nonwoven fabric having a porosity of at least 70% and a thickness of 20 μm to 100 μm, metallizing the nonwoven fabric with a coating comprising copper (Cu) via an electroless or electroplating process, followed by coating with a small amount of tin (Sn), palladium (Pd) and / or magnesium (Mg), and then obtaining a predominantly lithiophilic dendritic coating on the fibers by immersing the nonwoven fabric in a 0.1 MAgNO3 solution for a specified time (preferably 30 minutes), and forming a silver (Ag) dendritic layer on each fiber via a replacement reaction, thereby causing etching of copper (Cu) and electroplating of the silver (Ag) layer, and electroplating at a high current density (preferably 5 mA / cm 2 Up to 6mA / cm2 ) was used to electrochemically lithiate the nonwoven fabric.

[0031] The chemical replacement reaction can be given as

[0032] AgNO3+Cu→Ag+CuNO3s

[0033] The step of forming a predominantly lithiophilic coating preferably includes forming silver (Ag) dendrites to increase the surface area of ​​the porous bulk anode for nucleation and alloying reactions with lithium and / or other lithiophilic components.

[0034] Preferably, the anode is exposed to an applied magnetic field for a current greater than 70 mA / cm 2 The current density is greater than 70 mAh / cm 2 The areal capacity of the electrodes is enhanced by Li stripping and plating, where the magnetic field is applied along the transport direction of the charge carriers, i.e., parallel to the direction of the charge carriers.

[0035] Also provided is a lithium metal secondary battery comprising a porous 3D body anode as described, wherein the battery resides in a magnetic field for a current of greater than 70 mA / cm -2 The current density is greater than 70 mAh / cm 2 Enhanced lithium stripping and plating at high areal capacity.

[0036] The invention described herein allows the possibility of implementing a flexible 3D porous self-standing body for a lithium metal anode with fast charging capability. The body, as well as dendritic silver (Ag) and lithiophilic heteroatoms, enable uniform and dense lithium plating at high current density and high area capacity without observing any dendrite growth or battery short circuit. The body anode described herein provides a solution that is likely to be combined with any battery design (i.e., button cells, pouch cells, prismatic cells, and / or cylindrical cells). In addition, it may be easy to obtain and manufacture porous 3D body materials and their metallization and lithiophilic coating applications. The body anode described herein also provides the possibility of removing the commonly used copper current collector foil, which enhances the weight and volume energy density of the battery, wherein the 3D body itself acts as a current collector. In addition, fast charging capabilities that exceed the state of the art are also highly sought after, and the body described herein inherently provides these capabilities as well as enhanced safety.

[0037] The present invention paves the way for lithium / alkali metal anode secondary batteries with high C-rate capability, balanced N / P capacity ratio (lithium excess less than 50%), and fast charge / discharge, which have enhanced safety due to the alleviation of the dendrite problem commonly observed in secondary lithium metal anode batteries.

[0038] Further features, characteristics and advantages may be derived from the following discussion of test results with reference to the accompanying drawings, which show:

[0039] Figure 1a ) in an external magnetic field of 10 mT, at 71 mA / cm 1 and 71mAh / cm 1 Morphology of lithium plated into a free-standing, porous, 3D, flexible host anode at current density and areal capacity.

[0040] Figure 1b ) Electrochemical lithium plating curves of a free-standing, porous, 3D, flexible bulk anode at different current densities under a constant applied magnetic field of 10 mT.

[0041] Figure 1c ) Stripping-plating curves of a symmetric cell containing a free-standing, porous, 3D, flexible host anode according to the present invention using a current density and areal capacity of 5 mA / cm and 2.5 mAh / cm, respectively, without applying an external magnetic field.

[0042] Figure 1d ) Stripping-plating curves of a symmetric cell containing a free-standing, porous, 3D, flexible host anode according to the present invention using a current density and areal capacity of 6 mA / cm and 6 mAh / cm, respectively, without applying an external magnetic field.

[0043] Figure 1e ) Comparison of lithium plating curves on a copper current collector, a gold-plated copper current collector and a free-standing, porous, 3D, flexible bulk anode according to the present invention, at a constant applied magnetic field of 10 mT at current density and areal capacity of 20 mA / cm and 20 mAh / cm, respectively.

[0044] Figure 1f ) Galvanostatic charge-discharge curves of the LFP cathode against the 3D pre-lithiated porous 3D self-supporting host anode according to the present invention.

[0045] To demonstrate the performance of the bulk anode described within this invention, symmetric cells, i.e., cells assembled using two identical electrodes, one pre-charged and one discharged, with lithiated bulk anodes on both sides, were assembled and tested at different current densities and areal capacities.

[0046] The bulk anode consists of a 3D porous nonwoven fabric with a thin coating of a specific concentration and composition according to the present invention to form a lithiophilic surface that allows lithium electroplating at high current density and areal capacity once implemented in a secondary lithium metal battery and in an applied magnetic field, thereby allowing charging rates in excess of 10C, where battery C ratings (Cratings) are a measure of the current when the battery is charged and discharged. The capacity of a battery is usually rated and labeled at a 1C rate (1C current). This means that a fully charged battery with a capacity of 10Ah should be able to provide 10 amps in one hour.

[0047] More specifically, the porous 3D bulk anode consists of a bottom polymer fiber with a diameter ranging from 200 nm to 40 μm, 35 μm for the sample here, and fibers such as PAN, PP, PTFE, PEEK or PES that are stable to organic liquid electrolytes, polymer electrolytes, gel polymer electrolytes or ceramic electrolytes and lithium salts commonly used in secondary lithium metal or lithium ion batteries.

[0048] The fibers are then used to form a nonwoven fabric, which is then metallized. The metallized coating mainly contains copper (Cu) and possible lithiophilic heteroatoms tin (Sn), palladium (Pd), magnesium (Mg), etc.

[0049] To coat the material with a predominantly lithium-philic silver (Ag) coating, the 3D porous body was immersed in a 0.1 M AgNO3 solution for exactly 30 minutes to form a silver (Ag) layer on top of each fiber via a replacement reaction, resulting in etching of copper (Cu) and electroplating of the silver (Ag) layer containing silver (Ag) dendrites, which are crucial for further increasing the surface area of ​​the porous body for nucleation and alloying reactions with lithium, see Figure 1b .

[0050] Then, at 5 mA / cm 2 and 6mA / cm 2 The porous 3D host was electrochemically lithiated at a high current density of 5 mA / cm 2 For electrochemical lithiation at current densities of 40 mAh / cm 2 The area capacity of 10 mA / cm 2 Higher current densities are disadvantageous as this can lead to short circuits. These results were obtained on samples with a fiber diameter of 35 μm. This could potentially be further improved by reducing the fiber diameter and optimizing the density and alignment of the fibers. The electrochemically lithiated hosts were found to show planar or 2D growth of lithium.

[0051] Experimental data show that at 5 mA / cm 2 and 6mAcm2 The current density is 2.5 mAh / cm 2 and 6 / mAh cm 2 Symmetric cells cycled at areal capacities of 1000 and 500 cycles can be cycled, respectively. Figure 1c and d.

[0052] In contrast, the symmetric cell with lithium metal showed severe cycle decay and high stripping plating overpotential, thus clearly demonstrating the superior performance of the host described in this invention. In addition, post-mortem analysis of the host anode after 900 cycles clearly showed 2D planar plating of lithium, indicating the long-term stability of the host anode described herein.

[0053] To further enhance the performance of the 3D hosts described herein, symmetric cells with lithium 3D porous hosts were assembled and placed in a 10 mT magnetic field. Significant improvements in plating current density were observed compared to host anodes plated without a magnetic field.

[0054] Without a magnetic field, the porous 3D body can only maintain 10mA / cm 2 The current density was 20 min, however, electroplating could be easily extended to 1 h in a magnetic field. 2 The current density of 20, 50 and 70 mAh / cm 2 The excellent performance in a magnetic field is clearly demonstrated by plating lithium into the host at an area capacity of 1000 Å. Figure 1b .

[0055] In addition, by comparing the three samples (where the 2 The results show that the main structure plays a key role in the low nucleation potential of lithium electroplating (bare copper foil, gold (Au) copper foil and 3D main anode according to the present invention) with a current density of 1000 Å, showing that the main structure plays a key role in the low nucleation potential of lithium electroplating. It is worth mentioning that the magnetic field in all studies was applied in parallel and along the direction of lithium ion transport. The magnetic field was generated by a Helmholtz coil. In a 10mT magnetic field and at 53mA / cm 2 and 53mA / cm 2 The SEM micrograph of the 3D porous body electroplated at a current density of Figure 1e middle.

Claims

1. A self-supporting, porous, 3D, flexible host anode for a lithium metal secondary battery, having an open and accessible porosity of at least 70% and a thickness in the range of 10 μm to 100 μm, comprising a non-woven, woven or ordered arrangement of polymer fibers with a diameter in the range of 200 nm to 40 μm, and comprising silver (Ag) as the main lithiophilic constituent material exhibiting a dendritic morphology and a small amount of at least two additional lithiophilic materials such as tin (Sn), palladium (Pd); and / or magnesium (Mg), wherein the concentration of the additional lithiophilic materials is less than 5 atomic weight %, and wherein electrochemical lithiation results in the formation of one or more intermetallic alloys, thereby a high lithiated state and the coexistence of two phases, namely the intermetallic alloy and lithium metal, wherein the high lithiated state refers to a theoretical lithiated capacity exceeding the existing intermetallic phase.

2. The self-supporting, porous, 3D, flexible bulk anode of claim 1, wherein the silver (Ag) as the primary constituent material of the dendrites grows via a replacement or substitution reaction of a less noble metal present in an underlying layer.

3. A self-supporting, porous, 3D, flexible bulk anode according to claim 1 or 2, wherein the fibers are composed of metallized polymer fibers, which are stable to organic liquid electrolytes, polymer electrolytes, gel polymer electrolytes or ceramic electrolytes and lithium salts commonly used in secondary lithium metal or lithium ion batteries, wherein the fibers can be composed of polyacrylonitrile (PAN), polypropylene (PP), polytetrafluoroethylene (PTFE), polyetheretherketone or polyethersulfone (PES).

4. A self-supporting, porous, 3D, flexible bulk anode according to any of the preceding claims, wherein the silver (Ag) is provided as a layer comprising 1D, 2D, twinned and / or branched dendrites, thereby increasing the surface area of ​​the porous bulk anode for nucleation, alloying reaction and subsequent electroplating of alkali metals.

5. A method for preparing a self-supporting, porous, 3D, flexible main body anode for a lithium metal secondary battery, comprising the following steps: a. Providing a polymer fiber having a diameter of 200 nm to 40 μm and being stable to an organic liquid electrolyte, a polymer electrolyte, a gel polymer electrolyte or a ceramic electrolyte and a lithium salt commonly used in secondary lithium metal or lithium ion batteries, the fiber being, for example, polyacrylonitrile (PAN), polypropylene (PP), polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK) or polyethersulfone (PES); b. forming a nonwoven, woven or ordered fabric comprising said polymer fibers, said fabric having a porosity of at least 70% and a thickness between 20 μm and 100 μm; c. metallizing the fabric with a coating comprising copper (Cu) and a smaller concentration of a desired lithiophilic material, such as tin (Sn), palladium (Pd) and / or magnesium (Mg); d. forming a primary lithiophilic coating on the fibers by immersing the fabric in a 0.1 M AgNO3 solution for a specified time and forming a silver (Ag) layer on each fiber via a replacement reaction that results in etching of the copper (Cu) on the underlying seed layer and electroplating / growth of a dendritic silver (Ag) layer; and e. electrochemically lithiating the fabric at a high current density.

6. The method for preparing a self-supporting, porous, 3D, flexible bulk anode according to claim 5, wherein the prescribed time for immersing the nonwoven fabric in the 0.1 M AgNO3 solution is 30 minutes.

7. A method for preparing a self-supporting, porous, 3D, flexible bulk anode according to claim 5 or 6, wherein the step of forming a primary lithium-philic coating comprises 1D, 2D, twinned and / or branched silver (Ag) dendrites, thereby increasing the surface area of ​​the porous bulk anode for the nucleation, alloying and plating reactions with alkali metal ions.

8. The method for preparing a self-supporting, porous, 3D, flexible bulk anode according to any one of claims 5 to 7, wherein the high current density is 5 mA / cm 2 Up to 6mA / cm 2 .

9. A method for preparing a self-supporting, porous, 3D, flexible bulk anode according to any one of claims 5 to 8, wherein the anode is exposed to an applied magnetic field for a current of greater than 70 mA / cm 2 The current density is greater than 70 mAh / cm 2 Enhanced stripping and lithium plating under areal capacity, wherein the magnetic field is applied along the transport direction of the charge carriers, that is, parallel to the direction of the charge carriers.

10. A lithium metal secondary battery comprising a self-supporting, porous, 3D, flexible bulk anode according to any one of claims 1 to 4 and / or 5 to 9.

11. The lithium metal secondary battery of claim 10, wherein the battery is exposed to an external magnetic field for a current of greater than 70 mA / cm 2 The current density is greater than 70 mAh / cm 2 The areal capacity is enhanced under stripping and lithium plating, wherein the magnetic field is applied along the transport direction of the charge carriers, that is, applied parallel to the direction of the charge carriers.

Citation Information

Patent Citations

  • Alkali Metal Battery Having an Integral 3D Graphene-Carbon-Metal Hybrid Foam-Based Electrode

    US20170352868A1

  • Rechargeable batteries and methods of making same

    US20200274155A1

  • Anode protective layer compositions for lithium metal batteries

    US9722275B2

  • High energy density lithium metal based anode for solid-state lithium-ion batteries

    WO2021189083A1